Study on axial compression mechanical behavior of cold-formed thin-walled C-shaped steel composite wall sheathed with straw board on both sides. (October 2021) - Zhang, Xiuhua; Zhang, Enyuan; Li, Chaoran
Abstract: To examine the axial compression mechanical behavior of cold-formed thin-walled C-shaped steel (CFS) composite walls sheathed with straw board on both sides (CFSSB composite walls), this study conducted tests on 3 scale-model wall specimens to investigate the failure mode, axial load–displacement responses, and axial load-bearing capacity. The following parameters of the specimens were considered: stud spacing and presence of cement plaster mortar on the surface of the straw board in the specimens. In the tests, one specimen with cement plaster mortar was compared with the other two specimens, and the load–displacement curves and load–strain curves of the three specimens were obtained. The results indicated that the failure mode of the composite wall involved local buckling of the steel stud, partial bending and wrinkles on the straw board. In addition, the restrictive effect of the straw board on the steel frame increased the load-bearing capacity, and the mortar reduced the wrinkles on the straw board. On the basis of these findings, the finite element analysis (FEA) software program ABAQUS was used to analyze the axial compression performance of CFSSB composite walls, and factors affecting the bearing capacity were analyzed, such as the height-thickness ratio of the CFSSB wall, the section thickness of the C-shaped steel, and the stud spacing. A formula for calculating the axial bearing capacity of the CFSSB composite wall based on the test data and FEA results was established. The research conclusions can provide a reference for engineering applications with CFSSB composite walls.